A common ground? - Squires, Claire (Javnost (Ljubljana), 2004)
This article argues that research into literary prizes can potentially be extremely pertinent in the understanding of the material and ideological conditions of the production and reception of literature and literary value. As such, the analysis of prizes awarded is similar to the wider project of book history and publishing studies, and in their fusion of cultural and economic capital, literary prizes are thus part of the larger environment in which books are produced, distributed and consumed. Through an examination of the impact of eligibility requirements and the reception of prize-winning books, particularly within the European context, this article examines the vital role of prizes in the creation of communities of writers and the development of communities of readers. The article considers a variety of methodologies for the study of literary prizes. It calls for an analysis both quantitative and qualitative, and that pays attention to both the histories and development of individual prizes, and the wider negotiations book prize culture makes with the publishing industries and culture in general, both on the "common ground" of European and global prize cultures, and in its regionaland national differences.
Keywords: evropska književnost; literarne nagrade; knjige; prodaja; knjigotrštvo; založništvo